Phenotypic Screening to Identify Small‐Molecule Enhancers for Glucose Uptake: Target Identification and Rational Optimization of Their Efficacy. Issue 20 (1st April 2014) - Koh, Minseob; Park, Jongmin; Koo, Ja Young; Lim, Donghyun; Cha, Mi Young; Jo, Ala; Choi, Jang Hyun; Park, Seung Bum
Abstract: Small‐molecule glucose uptake enhancers targeted to myotubes and adipocytes were developed through a phenotypic screening linked with target identification and rational optimization. The target protein of glucose‐uptake enhancers was identified as a nuclear receptor PPARγ (peroxisome proliferator‐activated receptor gamma). Subsequent optimization of initial hits generated lead compounds with high potency for PPARγ transactivation and cellular glucose uptake. Finally, we confirmed that the chirality of optimized ligands differentiates their PPARγ transcriptional activity, binding affinity, and inhibitory activity toward Cdk5 (cyclin‐dependent kinase 5)‐mediated phosphorylation of PPARγ at Ser273. Using phenotype‐based lead discovery along with early‐stage target identification, this study has identified a new small‐molecule enhancer of glucose uptake that targets PPARγ. Abstract : A phenotype‐based discovery of initial hits enhances the cellular glucose uptake in myotubes and adipocytes. The target identification and rational optimization of initial hits can generate lead compounds with high potency for PPARγ transactivation and cellular glucose uptake. The chirality of optimized ligands differentiated their biophysical and biochemical activities toward PPARγ.